Preparation and magnetic properties of L10–FePt/TiO2 nanocomposite thin films - Kong, Ji-Zhou (2013)
FePt nanoparticles (NPs) have been encapsulated in the insulating and protective oxide matrix, using a sol–gel process, in order to prevent particles from agglomerating and sintering during the heat-treatment process required for the L10 ordering. The microstructural and ferromagnetic properties of FePt/TiO2 nanocomposites were characterized. The presence of oxide-matrix leads to more homogeneous microstructures and better magnetic properties. The short range positional order of the FePt NPs can be preserved upon annealing at 700 °C to possess higher room-temperature coercivities (HC = 3.7 kOe). Such nanocomposites with assemblies of high-coercivity magnetic nanoparticles are attractive for realizing new types of ultra-high-density data storage devices and magneto-composites.